2015
DOI: 10.1016/j.amjoto.2014.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngocutaneous fistula after total laryngectomy: A single-institution experience, 2001–2012

Abstract: Purpose The purpose of this study was to determine the incidence of and risk factors for pharyngocutaneous fistula in patients undergoing total laryngectomy at a single institution. Materials and methods The records of 59 patients undergoing primary or salvage total laryngectomy at our institution from 2001 to 2012 were retrospectively reviewed. Data collected included patient, tumor and treatment characteristics, and surgical technique. Risk factors were analyzed for association with pharyngocutaneous fistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 34 publications
3
45
1
Order By: Relevance
“…In a recent study, Benson et al (5) reported the incidence as 34%. Our incidence of PCF (20.2%), which is still high, lies within the mid-range of previous series (1,(5)(6)(7)(8).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In a recent study, Benson et al (5) reported the incidence as 34%. Our incidence of PCF (20.2%), which is still high, lies within the mid-range of previous series (1,(5)(6)(7)(8).…”
Section: Discussionsupporting
confidence: 64%
“…Supraglottic tumors were speculated to be a risk factor as they require extensive resections and complicate pharyngeal reconstruction (3,14). This finding was not verified in our study as was done in other studies (5,17).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Sixteen articles potentially fit for inclusion in the review were selected . Of these, 4 were excluded after a complete reading: the first was excluded because it did not provide data regarding the incidence of pharyngocutaneous fistula separately between the groups submitted to primary and salvage laryngectomy; the second article referred to the surgical technique description, with no comparative data; the third article presented a case series of patients already mentioned in another study included in this review; in the fourth article, various types of surgical flaps were used precluding the use of data on the PMMF . Thus, this review included data from 12 observational retrospective studies, including 742 patients (253 in the PMMF group and 489 in the control group; Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Other positive predictors have included performance of concurrent neck dissection, advanced tumor size, positive surgical margins, low postoperative hemoglobin, and preoperative tracheostomy …”
Section: Introductionmentioning
confidence: 99%